Characterization of the Exradin W1 scintillator for use in radiotherapy. Issue 1 (23rd December 2014) - Carrasco, P.; Jornet, N.; Jordi, O.; Lizondo, M.; Latorre‐Musoll, A.; Eudaldo, T.; Ruiz, A.; Ribas, M.
Abstract : Purpose: To evaluate the main characteristics of the Exradin W1 scintillator as a dosimeter and to estimate measurement uncertainties when used in radiotherapy. Methods: We studied the calibration procedure, energy and modality dependence, short‐term repeatability, dose‐response linearity, angular dependence, temperature dependence, time to reach thermal equilibrium, dose‐rate dependence, water‐equivalent depth of the effective measurement point, and long‐term stability. An uncertainty budget was derived for relative and absolute dose measurements in photon and electron beams. Results: Exradin W1 showed a temperature dependence of −0.225% °C −1 . The loss of sensitivity with accumulated dose decreased with use. The sensitivity of Exradin W1 was energy independent for high‐energy photon and electron beams. All remaining dependencies of Exradin W1 were around or below 0.5%, leading to an uncertainty budget of about 1%. When a dual channel electrometer with automatic trigger was not used, timing effects became significant, increasing uncertainties by one order of magnitude. Conclusions: The Exradin W1 response is energy independent for high energy x‐rays and electron beams, and only one calibration coefficient is needed. A temperature correction factor should be applied to keep uncertainties around 2% for absolute dose measurements and around 1% for relative measurements in high‐energy photon and electron beams. The Exradin W1 scintillator is an excellent alternative to detectors such as diodes for relative dose measurements.